Decolonial voices : Chicana and Chicano cultural studies in the 21st Century - Aldama, Arturo J., 1964-; Quiñonez, Naomi Helena (Latino literature., 2002)
The interdisciplinary essays in this volume discuss racialized, subaltern, feminist, and diasporic identities and the aesthetic politics of hybrid and mestiza/o cultural productions. The collection represents several key directions in the field: first, it charts how subaltern cultural productions of US/Mexico borderlands speak to the intersections of 'local', 'hemispheric', and 'globalized' power relations of the border imaginary. Second, it recovers the Mexican women's and Chicana literary and cultural heritages ignored by Euro-American canons and patriarchal exclusionary practices.